Dinamika Sikap Generasi Milenial Terhadap Bahasa Indonesia Pada Mahasiswa Fakultas Dakwah Unisba Angkatan 2022 - Dhiya Fauziyyah Ulya; Fidya Alfafa Aziz; Tazkiya Fathia Rahma (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Indonesian is not only a practical communication tool, but also an element of national identity that plays an important role in uniting individuals, groups, and society as a whole. The development of Indonesian has progressed rapidly, and millennials play a key role in this dynamic. The influence of the millennial generation is not only reflected in the use of everyday language, but also involves the creation of new words that reflect the changing times. The language behavior of the millennial generation, especially among students of the Faculty of Da'wah Class of 2022, is the focus of this study. Through descriptive analysis methods and quantitative analysis using online questionnaires, this study aims to examine the attitude of the millennial generation towards Indonesian. The results showed that this millennial generation They use Indonesian as a means of daily communication, and they find it important to maintain the authenticity of the language in an era of rapidly evolving technology. In this context, the millennial generation is expected to be agents who promote and maintain the sustainability of Indonesian. Despite the influence of slang and technological developments, the millennial generation of the Faculty of Da'wah Class of 2022 shows awareness of the importance of maintaining the authenticity of Indonesian as part of national identity. It is hoped that sustainability and sustainability of Indonesian can continue to be maintained through collaborative efforts and millennial generation's awareness of the importance of this cultural heritage.